Enhancement of the information system on categorized teacher materials and online examination with item analysis (enhanced examination online) - Yu, Lorraine Raissa Te. (2008)
The creation and management of examinations is one of the problems faced by teachers. Teachers carry heavier workload and manage more students per class. As a result, teachers cannot manage their time well and in effect, the create substandard examinations and have less time in monitoring their student?s performance. An online examination system, the Examination Online (EOL), has been effective in aiding teachers in creating and managing exams. However, the EOL has problems that have to be addressed: the need to be debugged, insufficiently of interfaces, and the lack of features for creating hard copies, exporting student records, and disseminating results to students. The study aimed to further ease the process of creation and management of exams by debugging the system, modifying the system, and adding new features. Debugging was done by adding error trapping conditions and recalculation of results. Modifying was done by adding text fields for inserting the highest possible score and the explanation for the answer, creating an interface for editing an exam, and creating a reviewer for students to see their exam results. The new feature added were the batch uploading of the files per type of exam, e-mailing of results to students, exporting results to new or existing file, creation of printable questionnaires, answer keys and answer sheets, and creation of rich text questionnaires and answer keys. As a result, the debugging, modifying and adding new features made the EOL more efficient and effective and a more effective tool learning. Despite its being efficient and effective, new features may still be added to the system. Some features could be the batch upload of an exam with the chapter and subject and type of exam specified, image inclusion in the creation of questions, inclusion of more questions types, allowing two or more possible answers for objective types of exams, and sending of results vi SMS
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2008
Keywords: Examination maker; Online examinations; Online exmination system; Online learning; EOL (Examination OnLine); Examination softwares